2019
DOI: 10.1002/smll.201901124
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Electronics Based on 2D Materials for Human Physiological Information Detection

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10. 1002/smll.201901124. Recently, advancement in materials production, device fabrication, and flexi ble circuit has led to the huge prosperity of wearable electronics for human healthcare monitoring and medical diagnosis. Particularly, with the emergence of 2D materials many merits including light weight, high stretchability, excellent biocompatibility, and high performance are used for those potential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 218 publications
(310 reference statements)
0
122
0
Order By: Relevance
“…These soft devices can be connected to skin surfaces or attached to biological tissues to monitor a variety of physiological signals such as limb motion, body temperature, pulse pressure, body sweat, breathing gas, and saliva. [263] However, these devices need to be constructed from flexible and even stretchable materials. Owing to their ultra-low thickness and large surface-to-volume ratio, 2D materials have been widely conformably integrated on human skin or in biological tissues to afford versatile wearable devices.…”
Section: Wearable Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…These soft devices can be connected to skin surfaces or attached to biological tissues to monitor a variety of physiological signals such as limb motion, body temperature, pulse pressure, body sweat, breathing gas, and saliva. [263] However, these devices need to be constructed from flexible and even stretchable materials. Owing to their ultra-low thickness and large surface-to-volume ratio, 2D materials have been widely conformably integrated on human skin or in biological tissues to afford versatile wearable devices.…”
Section: Wearable Devicesmentioning
confidence: 99%
“…Ti 3 C 2 T x has been used as a flexible electrode material enabling the actuation upon electrochemical process occurrence. [ 263 ] In‐depth research demonstrated that the expansion and shrinkage of the interlayer spacing of MXenes results in actuation. To develop multifunctional actuators, researchers studied the structure of leaves and developed a bilayer actuator based on Ti 3 C 2 T x ‐cellulose composites (MXCC) and a polycarbonate (PC) membrane ( Figure a,b).…”
Section: Bioelectronic Devices Based On 2d Materials Beyond Graphenementioning
confidence: 99%
“…There are evidences of versatile use of wearable devices for emerging applications in healthcare monitoring [24][25][26]. Various new sensors for healthcare tracking have been devised in the recent past for different purposes [27][28][29][30][31] and these devices have been used for various applications [32,33]. The commonly acknowledged applications of these wearable devices include mental health assessment [34] and sleep monitoring [35].…”
Section: Related Workmentioning
confidence: 99%
“…with flexible substrates in different ways. [1][2][3][4] Compared with the conventional rigid silicon-based electronics, this kind of electronics can withstand various deformations such as tension, compression, bending, and twisting, etc. Pressure sensors that can transduce external pressure into processing compatibility is urgently desired for the fabrication of flexible pressure sensors.…”
Section: Introductionmentioning
confidence: 99%